En syrisk kilde til den ældste kristne nadverforståelse – en analyse af Addai og Maris Nadverbøn - Munkholt, Maria (Dansk Teologisk Tidsskrift, 2010)
The Anaphora of Addai and Mari (A&M) is an ancient Syriac Eucharistic prayer. This article provides a Danish translation of the prayer and presents indications that A&M contains one of the oldest Eucharistic traditions that we know of. It is argued that A&M presents an understanding of the divine presence in the Eucharist that differs from traditional Western and Hellenistic views, and that A&M seems to be influenced by Jewish prayer forms. The article utilises A&M to discuss and broaden commonly held theories about the earliest understanding and development of the Eucharistic ritual.